Pediatric Mesenchymal Hamartomas of the Liver can Show Both Foregut and Hindgut Phenotype. (December 2017) - Wu, Hao; Ferguson, William; Castro, Eumenia; Finegold, Milton; Patel, Kalyani
Cystic epithelium in mesenchymal hamartoma (MH) is typically biliary type. Mucinous differentiation of the epithelium and increased hepatocellular component may pose a diagnostic challenge. We studied MH in 7 children (6 M, 1 F; age 4 months to 8 years, median 1 year). Resected tumors varied from 3.0 to 17.0 cm. All tumors showed biliary epithelium in the cystic component with strong and diffuse reactivity for CK7 and CK19. Expression of CK20 and CDX2 was additionally seen in 2 tumors, rare/focal in 1, and diffuse with mucinous differentiation in the other. Strong and continuous nuclear reactivity for Sox9 was seen in the cyst epithelium in all 7 tumors including focal staining in mucinous areas. It was also positive in the hepatocellular component. CD56 and vimentin were variably positive in the cystic epithelium of all cases. Alpha-fetoprotein showed patchy weak staining in the hepatocellular component and was negative in the cystic epithelium. Hepar-1 showed focal staining in the cystic epithelium in 4/7 cases and diffuse in the hepatocellular component. Both patients showing CK20 and CDX2 expression had abnormal chromosomal analysis: one with balanced translocation between chromosomes 2 and 19 and other with loss of chromosome Y. Among others, one showed 46, XY, inv(9)(p11q12), one did not grow cells, and the remaining 3 had normal karyotype. Six patients underwent resection and one had liver transplantation. All were alive and well with a median follow-up of 1.5 years. In conclusion, mucinous epithelium can be seen in MH. Expression of Sox9 in the cyst epithelium and hepatocytes suggests a common origin for these components. Expression of vimentin indicates an overlapping epithelial-mesenchymal phenotype. Hepatic MH can show divergent epithelial differentiation including both foregut and hindgut phenotype, which may provide insights into the pathogenesis of this rare neoplasm but does not seem to affect the outcome in this limited series.